Обучающая система по компьютерным графическим пакетам - Азаренков, В. И.; Костарев, Д. Б. (УАДО, 2002)
The computer tutorial system «Practical work at the course "Handling of the graphical information» is featured. The system is created with use multimedia and web-process technologies, allows to connect to it extra courses on this or that graphical package and has developed interactive and multimedia parts permitting to improve process of tutonng.
Keywords: обучающая система; компьютерный графический пакет